ANALISIS INTERAKSI SOSIAL ASOSIATIF DALAM BENTUK AKOMODASI ANTAR SANTRIWATI DI PANTI ASUHAN AL-ADABIY PONTIANAK - Dewi Mutia Arisanti; Rustiyarso Rustiyarso; Maria Ulfah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis thesis was titled : Analysis of Associative Social Interactions in the Form of Inter-Santriwati Accommodation at the Al-Adabiy Orphanage in Pontianak. A common problem in this research is how associative social interaction in the form of accommodation between students in the Al-Adabiy Nursing Home Pontianak. The sub-problems in this study were (1) How are associative social interactions between students in the form of accommodation arbitrarily at the Pontianak Al-Adabiy Orphanage? (2) How do associative social interactions between students in the form of accommodation tolerate the Al-Adabiy Orphanage in Pontianak? (3) What were the associative social interactions between students in the form of compromise accommodation at the Pontianak Al-Adabiy Orphanage? The purpose of this study is were to find out what forms were used by students in the form of accommodation at the Al-Adabiy Orphanage in Pontianak. The research method used was qualitative descriptive research. The research subjects were students who experienced associative social interaction disputes and coaches who deal with santri problems. Data collection techniques used were observation, interviews and documentation. Data analysis techniques in this study include data reduction, data presentation and verification/conclusion. The results showed the following findings: the form of associative social interaction in the form of accommodation found in this study constructors used three forms, namely accommodation in (1) arbitration, (2) tolerance and (3) compromise.Keywords : Accommodation, Associative Social Interaction, Santriwati